Perancangan dan Pembuatan Mesin Grinda Mantis Chip (GMC) Untuk Mengoptimalkan Proses Pengrindaan Chip Di PT. Promanufacture Indonesia - Nugroho, Oktavianus Ardhian; Antonio, Kevin Yonathan; Purwanto, Guruh (Manutech : Jurnal Teknologi Manufaktur, 2024)
PT. Promanufacture Indonesia is engaged in the field of biotechnology that produces laboratory equipment. One of the devices being developed is the Mantis-Tempest Chip (MTC) machine. In this tool, development, and modifications are made to the design of the chip. The chip developed is a laboratory instrument used for dispensing reagan with a microfluid system and can produce weight with precise volumes from various types of samples with a certain viscosity value. In the chip manufacturing process there is 1 process that is considered complicated, this process is a lasering process used to give a number to the chip. To carry out this process beforehand, it is necessary to carry out a surface smoothing process on the part to be lasered. So far, this process is still done manually by sanding the chips one by one. Therefore, the time required for the lasering process is long. The purpose of this research is to create a grinding machine that is specifically for the chip grinding process, with a position that can be adjusted the height of the grinding eye, this machine will later be used by the production division at PT. Promanufacture is in an effort to speed up the processing process and increase the speed and number of chips that can be lasered numbered. The results of this research were obtained a Grinding Mantis Chip (GMC) machine with dimensions of 170 x 110 x 50 mm, equipped with a grinda position that can be adjusted at a height of 45mm to 55mm, and can flatten the chip surface evenly, and consistently. In addition, the results of the GMC engine that has been made and tested can perform the process of scanning 6 chips simultaneously within 32 seconds so as to optimize the previously existing process.